2015
DOI: 10.1128/genomea.00927-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Porphyromonas gingivalis Strain A7436

Abstract: Porphyromonas gingivalis is strongly associated with periodontitis. P. gingivalis strain trafficking and tissue homing differ widely, even among presumptive closely related strains, such as W83 and A7436. Here, we present the genome sequence of A7436 with a single contig of 2,367,029 bp and a G+C content of 48.33%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Dowell, Jr., at the Centers for Disease Control and Prevention in Atlanta, GA, in the mid-1980s. Information source: http://www.ncbi.nlm.nih.gov/biosample/SAMN03366764 and Chastain-Gross et al ( 2015 )…”
Section: Methodsmentioning
confidence: 99%
“…Dowell, Jr., at the Centers for Disease Control and Prevention in Atlanta, GA, in the mid-1980s. Information source: http://www.ncbi.nlm.nih.gov/biosample/SAMN03366764 and Chastain-Gross et al ( 2015 )…”
Section: Methodsmentioning
confidence: 99%
“…To date, inconsistent amino acid sequences of a Fur homolog in P. gingivalis laboratory strains and clinical isolates identified based on genome sequencing have been deposited in databases. Among them are examples of 166-amino-acid-long proteins in W83 (AAQ65662) and TDC60 (BAK25731) (Nelson et al, 2003; Watanabe et al, 2011) and 200-amino-acid-long proteins in A7436 (AKV64657), ATCC 33277 (BAG34022), and JCVI SC001 (EOA10344) (Naito et al, 2008; McLean et al, 2013; Chastain-Gross et al, 2015; Figure 1). Experimental analysis performed by Butler et al (2014) employed a 166-amino-acid-long version of the P. gingivalis Fur homolog (termed Har) but possessing the amino acid sequence derived from the ATCC 33277 strain.…”
Section: Resultsmentioning
confidence: 99%
“…(B) Amino acid sequences of PgFur protein versions identified in P. gingivalis strains. Start codon of the longest protein version (MDR) deposited in databases is shown in blue (e.g., BAG34022 in ATCC 33277, EOA10344 in JCVI SC001, AKV64657 in A7436) (Naito et al, 2008; McLean et al, 2013; Chastain-Gross et al, 2015), the shortest protein version (MIV) deposited in databases is shown in green (e.g., AAQ65662 in W83, BAK25731 in TDC60) (Nelson et al, 2003; Watanabe et al, 2011), and the protein version identified in this study (MAV) is shown in red. The entire sequence of the PgFur protein and its mRNA identified in this study is shadowed.…”
Section: Resultsmentioning
confidence: 99%
“…To assign the potential function of the PgRsp protein, first bioinformatics approaches were employed. Searching for PgRsp-encoding sequences in P. gingivalis strains revealed that amino acid sequences deposited in databases for several P. gingivalis strains (e.g., W83, AJW4, ATCC 33277, 381, HG66, A7A1-28) predicted a 207-amino-acid version of the PgRsp protein, whereas in the A7436 strain a 283-amino-acid protein was predicted [49]. Our theoretical approaches and preliminary analysis of the 5 UTR region of the mRNA encoding PgRsp using 5 RACE (data not shown) led us to the conclusion that in the A7436 strain the pgrsp gene encodes a 207-amino-acid long protein.…”
Section: Pgrsp-a Heme-binding Member Of a Novel Family Of Crp/fnr Supmentioning
confidence: 99%